Identifying superusers of health services with mental health and addiction problems: Putting the Canadian Institutes of Health Research Strategy for Patient Oriented Research into action. (2017) - Quail, Jacqueline; Schaefer, Joelle; Neudorf, Cory; Anderson, Maureen; McLeod, Valerie; Lafontaine, Tania; Pelly, Judy; Baetz, Marilyn; Baker, Margaret; Teare, Gary; Muhajarine, Nazeem
No abstract available